2017
DOI: 10.1530/rep-17-0014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profiling of small RNAs of pig seminal plasma and ejaculated and epididymal sperm

Abstract: The similarities and differences of small RNAs in seminal plasma, epididymal sperm and ejaculated sperm remain largely undefined. We conducted a systematic comparative analysis of small RNA profiles in pig ejaculated sperm, epididymal sperm and seminal plasma and found that the diversity distribution of small RNA species was generally similar, whereas the abundance of small RNAs is dramatically different across the three libraries; miRNAs and small RNAs derived from rRNA, tRNA, small nuclear RNA, 7SK RNA, NRON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…, outlines the main functions of sperm RNA types in spermatogenesis and SPZ). [78] rsRNAs Mature SPZ are enriched in rsRNAs [50] rsRNAs are considered sperm quality biomarkers [49] Small RNA profiles in ejaculated sperm, epididymal sperm and seminal plasma indicate that sperm RNAs may have origins other than the testes [79] The deletion of a mouse tRNA methyltransferase, DNMT2, abolisheds sperm sncRNA-mediated transmission of high-fat diet (HFD)-induced metabolic disorders to offspring [80] Since SPZ are transcriptionally and translationally silent cells before departing the testes [81], it is plausible that the substantial remodeling of their ncRNA cargo may be driven extrinsically along the epididymis, a long convoluted tubule connecting rete testis to the vas deferens, composed of three main anatomical regions (caput, corpus and cauda), with a considerable segment to segment variation. Leading candidates to promote this crosstalk are epididymal epithelial cells that communicate with SPZ through epididymosomes, vesicles-heterogeneous in their lipid/protein/RNA composition and density-released through an apocrine secretory mechanism [82].…”
Section: Sperm Rna Codementioning
confidence: 99%
“…, outlines the main functions of sperm RNA types in spermatogenesis and SPZ). [78] rsRNAs Mature SPZ are enriched in rsRNAs [50] rsRNAs are considered sperm quality biomarkers [49] Small RNA profiles in ejaculated sperm, epididymal sperm and seminal plasma indicate that sperm RNAs may have origins other than the testes [79] The deletion of a mouse tRNA methyltransferase, DNMT2, abolisheds sperm sncRNA-mediated transmission of high-fat diet (HFD)-induced metabolic disorders to offspring [80] Since SPZ are transcriptionally and translationally silent cells before departing the testes [81], it is plausible that the substantial remodeling of their ncRNA cargo may be driven extrinsically along the epididymis, a long convoluted tubule connecting rete testis to the vas deferens, composed of three main anatomical regions (caput, corpus and cauda), with a considerable segment to segment variation. Leading candidates to promote this crosstalk are epididymal epithelial cells that communicate with SPZ through epididymosomes, vesicles-heterogeneous in their lipid/protein/RNA composition and density-released through an apocrine secretory mechanism [82].…”
Section: Sperm Rna Codementioning
confidence: 99%
“…This is clearly illustrated in our study with the SMARTer datasets, whereby 13,233 genes were identified. The small noncoding transcriptome of the porcine sperm has been recently described (Chen et al 2017). Chen and coauthors found a rich population of miRNAs and lower abundances of other families of small noncoding RNAs (e.g., rRNAs, tRNAs, snRNAs) but did not detect Piwi-interacting RNAs (piRNAs), a type of small noncoding RNAs with importantyet weakly exploredfunctions in sperm biology.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining mapped reads corresponded to snRNAs, piRNAs and tRNAs, among others (Table 4). Some of the most abundant miRNAs have already been identified in swine sperm or in other mammalian species and include miR10b and miR34c, among others (Jodar et al 2013;Capra et al 2017;Chen et al 2017).…”
Section: Rna-seq Library Preparation Sequencing and Mapping Statisticsmentioning
confidence: 99%
“…The top SNP for chromosomes 6 (rs43492923) and 7 (rs135631400) were close to 7SK, a small nuclear ribonucleoprotein coding gene (snRNA). This snRNA play role in DNA transcription and was found close to a significant SNP for bull fertility in chromosome 10 (Suchocki and Szyda, 2015), has a critical role in the control of primordial germ cells proliferation of mouse embryos (Okamura et al, 2012), and was detected in seminal plasma, ejaculated sperm and A c c e p t e d M a n u s c r i p t 13 epidydimal sperm in pigs with a significant biological role in spermatogenesis (Chen et al, 2017).…”
Section: Gene Annotation and Enrichment Analysismentioning
confidence: 99%